Lipid nanocarriers for microRNA delivery - Scheideler, Marcel; Vidakovic, Ivan; Prassl, Ruth (Chemistry and physics of lipids, 2020)
Non-coding RNAs (ncRNAs) like microRNAs (miRNAs) or small interference RNAs (siRNAs) with their power to selectively silence any gene of interest enable the targeting of so far ‘undruggable’ proteins and diseases. Such RNA molecules have gained much attention from biotech and pharmaceutical companies, which led to the first Food and Drug Administration (FDA) approved ncRNA therapeutic in 2018. However, the main barrier in clinical practice of ncRNAs is the lack of an effective delivery system that can protect the RNA molecules from nuclease degradation, deliver them to specific tissues and cell types, and release them into the cytoplasm of the targeted cells, all without inducing adverse effects. For that reason, drug delivery approaches, formulations, technologies and systems for transporting pharmacological ncRNA compounds to achieve a diagnostic or therapeutic effect in the human body are in demand. Here, we review the development of therapeutic lipid-based nanoparticles for delivery of miRNAs, one class of endogenous ncRNAs with specific regulatory functions. We outline challenges and opportunities for advanced miRNA-based therapies, and discuss the complexity associated with the delivery of functional miRNAs. Novel strategies are addressed how to deal with the most critical points in miRNA delivery, such as toxicity, specific targeting of disease sites, proper cellular uptake and endosomal escape of miRNAs. Current fields of application and various preclinical settings involving miRNA therapeutics are discussed, providing an outlook to future clinical approaches. Following the current trends and technological developments in nanomedicine exciting new delivery systems for ncRNA-based therapeutics can be expected in upcoming years.
Online 2 November 2019
Gesehen am 07.05.2020